METHOD FOR EVALUATION OF POWER-EFFICIENCY IN RECONSTRUCTION AND CONSTRUCTION OF OIL PIPELINE PART - Yu. N. Kolesnik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper describes a method and presents nomographs for determination of power-efficiency of oil pipeline operation in the case of transition from one pipeline system configuration to another one. This method is based on the usage of new configuration characteristics of a linear part of multi-line oil pipeline. It allows to analyze only the changed part of the pipeline system. The proposed configuration characteristics are based on recalculation of the length of input/output pipeline with specific diameter to the similar length of the pipeline with a conventional diameter and it is numerically equal to an extent of a laid pipeline with a conventional diameter from an initial time moment t0 to a time moment t.